CONTINUOUS MIDWIFERY CARE FOR MRS. R WITH THE APPLICATION OF WARM COMPRESS DURING PREGNANCY IN THE WORKING AREA OF THE PACET PUBLIC HEALTH CENTER BANDUNG REGENCY - Nadhaafa Nur Karliena; Yulia Ulfah Fatimah; Ida Widiawati; Yulidar Yanti (Politeknik Kesehatan Kemenkes Bandung, 2026)
Background: Continuity of midwifery care is provided during pregnancy, childbirth, postpartum, newborn and family planning. In the case of Mrs. R at the Pacet Community Health Center, warm compresses were used during pregnancy to address back pain caused by postural changes and fetal pressure. Warm compresses can increase blood flow, reduce muscle tension, and have a relaxing effect on maternal physical comfort. Care was continued through postpartum and the newborn period, implementing evidence-based midwifery management. Objective: This report aims to provide continuous care by applying warm compresses during Mrs. R's pregnancy at the Pacet Community Health Center. Methods: This report presents a case study of continuous midwifery care practices, comprising a comprehensive report of evidence-based continuous midwifery care. Results: The mother received three antenatal care visits during her pregnancy. At 39 weeks of pregnancy, she experienced back pain, which was addressed with warm compress therapy. At 40 weeks and 2 days of gestation, a complication of oligohydramnios was discovered, requiring hospitalization. Further examination indicated fetal distress, leading to a cesarean section. The baby was then hospitalized for three days due to infection. The mother's choice of contraception after the cesarean section was an intrauterine device (IUD). Conclusion: Warm compresses can reduce lower back pain in pregnant women. The mother's delivery, which involved oligohydramnios and fetal distress, was performed by cesarean section. The baby was hospitalized for three days due to leukocytosis. She was given cefotaxime and breastfed on demand. During the postpartum period, the mother experienced breast engorgement, which was successfully addressed with breast care. Recommendation: Healthcare workers should continue to improve the quality of care in providing continuous midwifery care.